1997
DOI: 10.1590/s0100-84041997000200010
|View full text |Cite
|
Sign up to set email alerts
|

Monostromatic green algae (Ulvales, Chlorophyta) of São Paulo and Paraná states (Brazil): distribution, growth, and reproduction

Abstract: -(Monostromatic green algae (Ulvales, Chlorophyta) of São Paulo and Paraná states (Brazil): distribution, growth, and reproduction). Culture studies were used for taxa identification and to understand aspects of the biology and physiology of monostromatic green blades growing in various sites along the coast of São Paulo state (23 RESUMO -(Algas verdes monostromáticas (Ulvales, Chlorophyta) dos estados de São Paulo e Paraná (Brasil): distribuição, crescimento e reprodução). Estudos em cultura foram usados par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
4
1
1
Order By: Relevance
“…Leskinen et al (2004), working with Ulva intestinalis and Ulva compressa in the Baltic Sea, used halotolerance as an additional character, besides genetic variation using internal transcribed spacer (ITS) markers, to distinguish morphological plastic species with overlapping characters. Based on the systematics of the genus Monostroma described by Tatewaki (1972) -Marino et al 1993;Braga et al 1997), which were considered as eurythermic and euryhaline species. These physiological responses are typical of monostromatic green seaweeds that are distributed mainly in estuaries of subtropical and temperate zones and are subjected to a broad fluctuation of salinity (Biebl 1937).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leskinen et al (2004), working with Ulva intestinalis and Ulva compressa in the Baltic Sea, used halotolerance as an additional character, besides genetic variation using internal transcribed spacer (ITS) markers, to distinguish morphological plastic species with overlapping characters. Based on the systematics of the genus Monostroma described by Tatewaki (1972) -Marino et al 1993;Braga et al 1997), which were considered as eurythermic and euryhaline species. These physiological responses are typical of monostromatic green seaweeds that are distributed mainly in estuaries of subtropical and temperate zones and are subjected to a broad fluctuation of salinity (Biebl 1937).…”
Section: Discussionmentioning
confidence: 99%
“…Monostromatic green algae in Brazil have been identified as Ulvaria oxysperma (Kützing) Bliding, or Monostroma oxyspermum (Kützing) Doty in previous reports (e.g., Joly 1965;Cordeiro-Marino et al 1993;Braga 1997;Braga et al 1997). However, Pellizzari (2005) studied two populations of monostromatic green algae from mangroves and estuaries of the Paraná coast, and concluded that both populations should be assigned to the genus Gayralia K.L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O trabalho foi objeto da dissertação de mestrado de Coto (2007) que consistiu de um levantamento da flora e comparação desta com os estudos pioneiros de A. B. Joly para a Baía de Santos (Joly 1957) e o Litoral Norte (Joly 1965), do Litoral Sul de Ugadim (1973) e do estudo de Ulvales para o estado, de Kanagawa (1983), além de estudos pontuais, tais como Oliveira Filho e Berchez (1978), Berchez & Oliveira (1992), Braga et al (1997), Qi (1999) …”
Section: Metodologiaunclassified
“…Information about monostromatic green seaweeds in Brazil is scarce. Braga et al (1997) reported on the reproduction of two species of monostromatic green algae, Cordeiro-Marino et al (1993) cultured Monostroma sp. in the laboratory, and Braga (1997) studied the colonization of two species of Monostroma-like algae on various substrates in the southern coast of São Paulo state.…”
Section: Introductionmentioning
confidence: 99%